Novel Application of Recommendation Standards to Evaluate a Cancer-Specific Community-Based Exercise Program. Issue 1 (13th January 2022) - Wood, Kelley C.; Leach, Heather J.; Marshall, Timothy; Hidde, Mary C.; Crisafio, Mary E.; Pergolotti, Mackenzi
Abstract : Supplemental digital content is available in the text. ABSTRACT: Lack of standards to regulate community-based supervised exercise programs (CSEP) is a barrier to improved integration in oncology. To foster standards development, we applied 11 recommended (non–cancer-specific) standards as a framework to describe and evaluate the Fitness Therapy (Fit) for Cancer Program. This study used descriptive, pre- and postevaluation of the Fit Cancer program—an 8-wk CSEP, including weekly group-based exercise and three physical activity (PA) behavior change discussion sessions. Outcomes collected pre- and postprogram include self-reported PA (vigorous, moderate, and walking minutes per week), well-being, lower body muscular endurance measured by 30-s sit to stand (30-STS), and program satisfaction (survey and open-ended program "highlights"). PA, 30-STS, and well-being were analyzed descriptively (mean, median, etc.), then pre- and postprogram change was evaluated using paired t -tests and Cohen's d . Program satisfaction data were analyzed using descriptive, sequential mixed method analysis with line-by-line inductive coding. The implementation of Fit Cancer aligned with each recommended standard (comprehensive screening and enrollment, evidence-based, small group, etc.). From 2017 to 2019, 46 participants completed the program (76.1% female, M age = 57 ± 10 yr). Significant pre- and postimprovements were observed for vigorous PA ( P = 0.00, d = 0.62), moderate PA ( P = 0.001, d = 0.07), 30-STS ( P = 0.00, d = 0.62), and well-being ( P = 0.008, d = 0.27). All respondents ( n = 32, 70%) agreed that they "enjoyed" the program, "looked forward to exercise sessions, " and the "staff and group environment provided a sense of community and support" that was beneficial. Themes in program "highlights" aligned with the recommended standards and included instructors, social support, exercise sessions, observable health/wellness impacts, and other supports (education, cost, resources). The Fit Cancer program aligns well with recommendation standards for CSEP and resulted in improved PA, lower body muscular endurance, and well-being for survivors. Results of this study provide pragmatic evidence to guide the development of future cancer-specific CSEP standards.